Hybrid clipping and companding techniques based peak to average power ratio reduction in orthogonal frequency division multiplexing based differential chaos shift keying system - Sejjad Razzaq Alqassab; Fadhil Sahib Hasan (Institute of Advanced Engineering and Science, 2022)
In this paper, a hybrid approach using clipping and companding techniques is introduced to reduce the peak to average power ratio (PAPR) of orthogonal frequency division multiplexing based differential chaos shift keying (OFDM-DCSK), which is the major drawback of the OFDM-DCSK. The hybrid function is processed at the end of the transmitter before transmitting the signal. However, there is no need for an inverse function at the receiver, which decreases the system complexity. Several techniques have been proposed in the literature for decreasing the PAPR value. Clipping and companding are active methods in terms of reducing the PAPR. Finally, the PAPR reduction and bit error rate (BER) performances are evaluated. The simulation results show that this technique gives better performance as compared with the clipping and companding techniques.